RANCANGAN MOTION DETECTOR DENGAN SENSOR PIR (PASSIVE INFRARED RECEIVER) DAN KAMERA MENGGUNAKAN ARDUINO UNO BERBASIS SMS GATEWAY PADA ANTENNA DISTRIBUTION UNIT LOCALIZER DI BANDARA HALIM PERDANAKUSUMA - Alfin Fandriana,; Soebroto,; R. Pugirkhan Yasin, (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
Flight safety and security is the responsibility and main objective of every airport for all flights it operates. To achieve this goal, every airport requires various types of sophisticated and reliable supporting equipment to support the realization of aviation safety and security. The Antenna Distribution Unit in the Localizer at Halim Perdanakusuma Airport does not have any security equipment for the ADU. Therefore, the author designed a device in the form of a motion detctor using Arduino Uno as a main control of PIR (Passive Infrared Receiver) and Camera for detecting movement, as well as a USB Cable that serves to transmit image data to a PC or Laptop and also an SMS Gateway that serves to providing information to technicians it is expected that thi motion detector can improve security at the Localizer Antenna Distribution Unit and make it easier for technicians to supervise the equipment is the responsibility of the technisian so that flight safety is maintained.